Contemporary morphological patterns: morphometric analysis of open spaces in different types of urban lots in the city of Uberlândia-MG - Cocozza, Glauco de Paula; Guerra, Maria Eliza Alves (National Journal of City Management, 2021)
The main objective of this study is to explore the influence and reflexes of urban and environmental legislation on the production, configuration, and distribution of urban open spaces. The work is based on the premise that, over the last years, legislation has played an important role in the composition of the urban spatial mosaic, especially regarding the need and obligation of all new lots to reserve, in the lottable land, a minimum percentage of open spaces, understood in this research as the road network, public recreation areas, permanent environmental protection areas, municipal easements and property easements. The object of this observation are the urban lots approved by the city of Uberlândia since 2000, a period in which several factors forced the city to adjust to the new urban development instruments and to the master plan, mainly the city’s rapid growth, also a result of the growth of the Brazilian real estate market. We applied the morphometric methodology, using the QGIS software to quantify open space and analyze measurements and rates of the morphological elements based on the legal parameters. The result was the identification of the way open spaces were designed in the analyzed projects, their spatial relations, morphological typology and distribution patterns, uncovering recurring patterns that characterize the landscape of many medium-sized Brazilian cities.